Occupational Therapists' Attitudes, Knowledge, and Implementation of Evidence-Based Practice: A Systematic Review of Published Research. (January 2014) - Upton, Dominic; Stephens, Danielle; Williams, Briony; Scurlock-Evans, Laura
Introduction: Evidence-based practice is the procedure whereby clinicians incorporate best research evidence, clinical expertise, and patient values to provide best patient care. Recently, there has been a significant push towards occupational therapists' adoption of evidence-based practice. This systematic review aimed to determine occupational therapists' attitudes, knowledge, and utilization of evidence-based practice. Method: A search of literature published between 2000–12 was conducted in relation to occupational therapists' practice. Academic Search Complete, Cumulative Index of Nursing and Allied Health Literature Plus, PsycARTICLES, Ingenta, Medline, Science Direct, and Journal Storage were systematically searched using MeSH and free-text keywords. Google Scholar and reference lists were also searched. Findings: Thirty-two papers were selected for review: 23 were quantitative, 8 were qualitative, and 1 used a mixed methods design. Studies demonstrated that occupational therapists hold positive attitudes towards evidence-based practice. However, these attitudes do not translate into practice, with research indicating a lack of evidence-based practice utilization. Occupational therapists perceive a number of barriers to evidence-based practice, including lack of time, lack of availability and accessibility of research, and having limited research skills. Conclusion: It is essential that educational and training initiatives provide therapists with the tools and support they need to engage fully with research evidence and its application within clinical care.